STRATEGI KOMUNIKASI ORGANISASI DALAM MENGOPTIMALISASI KETATALAKSANAAN PADA PT. PELINDO REGIONAL 4 (PERSERO) - Putri Atalia , Sri; Ahdan, Ahdan; Zelfia, Zelfia (UNIVERSITAS MUSLIM INDONESIA, 2022)
This Research aims to describe the Strategy of Communication Organizational for Optimizing the Structures in PT. Pelindo Regional 4 (Persero). The type of research used is descriptive qualitative. The data of this research consists of primary and secondary data. Primary data is obtained from interviewa, while secondry data is obtained by writing decoments and literature related to the object of research, data obtained and analyzed qualitative, namely by explaining the problems discussed in the thesis. The results of this research show that the Strategy of Communication Organizational for Optimizing the Structures in PT. Pelindo Regional 4 (Persero) has been running well, employees continue to improve their quality by improving the organization’s communication strategy. With the approach of communication strategies, the implementation of biased work much more productive